Multiparametric influence of 3D-printed organo-mineral scaffolds on bone regeneration - Touya Nicolas; Reiss Ségolène; Rouillon Thierry; Dutilleul Maeva; Veziers Joelle; Pare Arnaud; Brasset Ludmila; Weiss Pierre; Corre Pierre; Charbonnier Baptiste (Scientific Reports, 2024)
Abstract The development of synthetic bone substitutes that equal or exceed the efficacy of autologous graft remains challenging. In this study, a rat calvarial defect model was used as a reference to investigate the influence of composition and architecture of 3D-printed cement, with or without bioactives, on tissue regeneration. Printable cement pastes were formulated by combining hyaluronic acid and cement precursors. Cementitious scaffolds were printed with 3 different patterns. After 7 weeks of implantation with or without bone marrow, multiparametric qualitative and quantitative assessments were performed using µCT, SEM, and histology. None of the set-up strategies was as efficient as autologous cancellous bone graft to repair calvarial defects. Nonetheless, the presence of scaffold improved the skull vault closure, particularly when the scaffold was soaked in total bone marrow before implantation. No significant effect of scaffold macro-architecture was observed on tissue mineralization. Magnesium phosphate-based scaffolds (MgP) seemed to induce higher bone formation than their calcium-phosphate-based counterparts. They also displayed a quicker biodegradation and sparse remaining material was found after 7 weeks of implantation. Although further improvements are required to reach clinical settings, this study demonstrated the potential of organo-mineral cements for bone regeneration and highlighted the peculiar properties of MgP-based cements.